Reasons for Frequent Emergency Department Use by Medicaid Enrollees: A Qualitative Study. (30th March 2016) - Capp, Roberta; Kelley, Lauren; Ellis, Peter; Carmona, Juan; Lofton, Adrienne; Cobbs‐Lomax, Darcey; D'Onofrio, Gail
Abstract: Background: The Affordable Care Act initiated several care coordination programs tailored to reduce emergency department (ED) use for Medicaid‐enrolled frequent ED users. It is important to clarify from the patient's perspective why Medicaid enrollees who want to receive care coordination services to improve primary care utilization frequently use the ED. Methods: We conducted a qualitative data analysis of patient summary reports obtained from Medicaid enrolled frequent ED users who agreed to participate in a randomized control trial (RCT) evaluating the impact of patient navigation intervention compared with standard of care on ED use and hospital admissions. We defined frequent ED users as those who used the ED four to 18 times in the past year. The study was conducted at an urban, teaching hospital ED with approximately 90, 000 visits per year. The research staff conducted interviews (~30–40 minutes), regarding the patient's medical history, reasons for ED visits, health care access issues, and social distresses. The aforementioned findings were summarized in a 1‐ to 2‐page report and presented to the RCT's project team (social worker, emergency medicine physician, primary care physician, and patient navigators) on a weekly basis to further understand the needs of this patient population. A diverse team of researchers (program staff and physicians) coded all reports and reached consensus using reflexive team analysis. We reconciled differences in code interpretations and generated themes. Results: One‐hundred patients enrolled in the RCT from March 2013 to February 2014, and all 100 patient summary reports were evaluated. We identified three key themes associated with Medicaid enrollee frequent ED use: 1) negative personal experiences with the healthcare system, 2) challenges associated with having low socioeconomic status, and 3) significant chronic mental and physical disease burden. Conclusions: Medicaid frequent ED users engaged in receiving patient navigation services with the goal to reduce ED use and hospital admissions describe barriers that go beyond timely primary care access issues. These include sociodeterminants of health, lack of trust in primary care providers, and healthcare system.